EXTENDED HILDEBRAND SOLUBILITY APPROACH FOR NAPROXEN SOLUBILITY ESTIMATION IN ETHANOL + WATER COSOLVENT MIXTURES - ARAGON N., Diana M.; PACHECO A., Diana P.; RUIDIAZ M., Millar A.; SOSNIK, Alejandro D.; MARTÍNEZ R., Fleming (Vitae, 2009)
Naproxen (NAP) is a widely used non-steroidal anti-inflammatory drug; however their physicochemical properties have not been thoroughly studied. In this work, Extended Hildebrand Solubility Approach (EHSA) developed by Martin et al was applied to evaluate the solubility of NAP in ethanol + water cosolvent mixtures at 298.15 K ± 0.05 K. Molar volume and solubility parameter values of NAP, were calculated according to Fedors and van Krevelen methods. A good predictive capacity of EHSA was found using regular polynomial models in fifth order for NAP, when the W interaction parameter is related to the solubility parameter of the cosolvent mixtures. Nevertheless, deviations on estimated solubility obtained respect to experimental solubility values had shown the same order compared with those obtained directly by logarithm empirical regression means of experimental solubilities as a function of cosolvent solubility parameters